Phosphorylation of the androgen receptor at Ser81 is co‐sustained by CDK1 and CDK9 and leads to AR‐mediated transactivation in prostate cancer. Issue 7 (3rd May 2021) - Gao, XinTao; Liang, Jiaqian; Wang, LiYang; Zhang, Zhaoyang; Yuan, Penghui; Wang, Jiaxin; Gao, Yanfei; Ma, Fen; Calagua, Carla; Ye, Huihui; Voznesensky, Olga; Wang, Shaogang; et al.
Abstract : Androgen receptor (AR) is the principal molecule in prostate cancer (PCa) etiology and therapy. AR re‐activation still remains a major challenge during treatment of castration‐resistant prostate cancer (CRPC) tumors that relapse after castration therapies. Recent reports have indicated the enrichment of Ser81‐phosphorylated AR (pS81) in the nucleus of CRPC cells, and CDK1 and CDK9 as the kinases phosphorylating AR at S81. In the current study we showed that pS81 is preferentially localized in the nucleus in both rapid biopsy metastatic CRPC samples and PCa xenografts, and nuclear pS81 localization is correlated with AR transactivation in tumor xenografts. Chromatin immunoprecipitation (ChIP) analysis demonstrated an alignment of S81 phosphorylation and AR‐mediated transactivation with the chromatin locus openness. Moreover, pS81‐specific ChIP‐Seq showed a disproportional occupancy of pS81 on AR‐activated promoters, while 3C‐ChIP assays further indicated an enrichment of pS81 at the PSA enhancer‐promoter loop, a known AR activating hub. In the latter, CDK9 was shown to modulate the transactivation of the AR and RNA Pol II. Indeed, ChIP and re‐ChIP assays also confirmed that AR‐dependent activation of the PSA enhancer and promoter mediated by pS81 was coupled with activation of Pol II and the pTEFb complex. Mechanistically, we determined that CDK1 and CDK9 sustained the pS81 AR modification in the soluble and chromatin‐bound fractions of PCa cells, respectively. Finally, we demonstrated that CDK1 activity was maintained throughout the cell cycle, and that CDK1 inhibitors restored androgen sensitivity in CRPC tumor cells. Based on these findings, CDK1 and CDK9 could be targeted as pS81 kinases in patients with CRPC, either alone or in conjunction with direct AR antagonists. Abstract : Androgen receptor (AR) is phosphorylated at Ser81 (pS81) in prostate cancer. By using chromatin immunoprecipitation analyses (ChIP, ChIP‐seq, reChIP and 3C‐ChIP), we demonstrated that pS81 is coupled to AR transactivation and enriched at AR‐activated enhancer‐promoter loops. pS81 is co‐stimulated by CDK1 and CDK9, both representing potential therapeutic targets in castration‐resistant prostate cancer patients, either alone or in conjunction with direct AR antagonists.